Compliments in The Yemeni Society: a sociolinguistic perspective - Nada Qanbar, (Penerbit UKM, 2012)
This paper is a wide-range empirical investigation of the compliment behavior in the Yemeni speech community. It seeks to investigate its distribution, the structures and syntactic patterns of a compliment expression, the attributes praised, and how compliment is influenced by the sex and social status of both the complimenter and the receiver of the compliment. The corpus of the study consists of 400 compliments collected by the author through an ethnographic method. 20 students studying at Taiz University in Yemen participated in the study. The study reveals that a compliment in Yemeni society is formulaic. 65.75% of compliments in Yemeni Arabic fall into major identifiable syntactic patterns and 55% of the compliments contain adjectives, almost two thirds of which are fixed adjectives. This formulaic nature of compliments in Yemeni society supports that their function is to consolidate solidarity and maintain relationship. The corpus also reveals that 60% of compliments occur among females, and the majority of compliments are on ‘Appearance’, followed by ‘Personal Traits’. The majority of compliments are paid and received among equal status, and the least frequent compliments are given by lower status to higher status.